Im trying to work out that a Hadamard transform H (a unitary matrix) is its own inverse by applying it twice to an arbitrary state $|x⟩$:

$$H|x⟩ = \frac{1}{\sqrt{2^n}}\sum_{y \in \{0,1\}^n}(-1)^{x \cdot y}|y⟩\,.$$

Then \begin{align*} H\left(\frac{1}{\sqrt{2^n}}\sum_{y \in \{0,1\}^n}(-1)^{x \cdot y}|y⟩\right) &= \frac{1}{2^n}\sum_{y \in \{0,1\}^n} (-1)^{x \cdot y}\sum_{z \in \{0,1\}^n}(-1)^{y \cdot z}|z⟩\\ &=\frac{1}{2^n}\sum_{y \in \{0,1\}^n}\sum_{z \in \{0,1\}^n} (-1)^{x \cdot y}(-1)^{y \cdot z}|z⟩\\ &= \frac{1}{2^n}\sum_{y \in \{0,1\}^n}\sum_{z \in \{0,1\}^n}(-1)^{y \cdot (x + z)}|z⟩\,. \end{align*}

But I don't know how to get from here to $|x⟩$ again.

I know that $HH^* = I$, but I want to show it this way, to understand what is happening.


Rewrite your final expression as $$ \sum_{z \in \{0,1\}^n} \left| z \right\rangle \cdot \frac{1}{2^n} \sum_{y \in \{0,1\}^n} (-1)^{y \cdot (x+z)}. $$ So to complete the proof, we need to show that $$ \sum_{y \in \{0,1\}^n} (-1)^{y \cdot (x+z)} = \begin{cases} 2^n & \text{if } x=z, \\ 0 & \text{otherwise}. \end{cases} $$ If $x=z$ then $x+z = 0$ (computing modulo 2!), and so $(-1)^{y \cdot (x+z)} = 1$ for all $y$, hence the sum equals $2^n$. If $x \neq z$ then pick some $i$ such that $x_i \neq z_i$. We can partition $y$ into the $i$th coordinate $y_i$ and all the rest $y_{-i}$. Now $$ \sum_{y \in \{0,1\}^n} (-1)^{y \cdot (x+z)} = \sum_{y_{-i} \in \{0,1\}^{n-1}} (-1)^{y_{-i} \cdot (x+z)_{-i}} \sum_{y_i \in \{0,1\}} (-1)^{y_i \cdot (x+z)_i} = 0, $$ since $x_i+z_i = 1$ (modulo 2) and $\sum_{y_i \in \{0,1\}} (-1)^{y_i} = 1-1=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.